Phytoplankton composition in the fluvial-lagoon systems pom-atasta and palizada del este, adjacent to the terminos lagoon campeche, méxico (2014)
ABSTRACT The composition and abundance of phytoplankton community, and its relation to physical and chemical factors was evaluated in the fluvial-lagoon systems Pom-Atasta (PA) and Palizada del Este (PE), in February, 2011. Water samples were collected in ten sampling sites in each lagoon, with a van Dorn bottle at the surface and in the middle of the water column to measure temperature, salinity, dissolved oxygen, inorganic nutrients, chlorophyll a and the composition and abundance of phytoplankton. In order to describe the behavior of phytoplankton it was calculated species abundance, Shannon-Wiener diversity and Pielou equitability indices were used, and to analyze the relationship between the abundance of phytoplankton species and environmental variables, a canonical correspondence analysis (CCA) was applied. The results showed that PE was the lagoon that presented a great biodiversity with 348 identified taxa, maximum abundance values (269 × 103 cells L-1), H’ (3.2) and J’ (0.95). Cylindrotheca closterium was the most abundant species in both systems, observing the highest abundance (52.5 × 103 célls L-1) in PA, forming incipient toxic algal blooms. It should be noted that salinity was the most influential environmental variable in the composition and abundance of phytoplankton. RESUMEN Se evaluó la composición y la abundancia de la comunidad fitoplanctónica y su relación con los factores físicos y químicos en los sistemas fluvio-lagunares Pom-Atasta (PA) y Palizada del Este (PE). En febrero de 2011, se recolectaron muestras de agua, tanto en la superficie como a medio fondo, en diez sitios para cada laguna, utilizando una botella van Dorn, para medir la temperatura, salinidad, oxígeno disuelto, nutrientes inorgánicos, clorofila a, y la composición y abundancia de la comunidad fitoplanctónica. Para describir el comportamiento del fitoplancton se calculó la abundancia de las especies, el índice de diversidad de Shannon (H’) y la equidad de Pielou (J’). Para analizar la relación de la abundancia de las especies con respecto a las variables ambientales se aplicó un análisis de correspondencias canónicas. Los resultados mostraron, que PE fue la laguna que presentó la mayor diversidad de especies, con 348 taxa, y los valores más altos de abundancia (269 × 103 céls L-1), de H’ (3,2) y de J’ (0,95). Cylindrotheca closterium fue la especie más abundante en los dos sistemas, presentando su mayor abundancia (52,5 × 103 céls L-1) en PA, formando incipientes florecimientos algales no tóxico. La salinidad fue la variable ambiental que más influyó en la composición y abundancia del fitoplancton.